Curcumin, a Multi-Ion Channel Blocker That Preferentially Blocks Late Na+ Current and Prevents I/R-Induced Arrhythmias - Song, Lv; Zhang, Ze-fu; Hu, Liang-kun; Zhang, Pei-hua; Cao, Zhen-zhen; Liu, Zhi-pei; Zhang, Pei-pei; Ma, Ji-hua (Frontiers in Physiology, 2020)
Increasing evidence showed that Curcumin (Cur) has a protective effect against cardiovascular diseases. However, the role of Cur in the electrophysiology of cardiomyocytes is currently not entirely understood. Therefore, the present study was conducted to investigate the effects of Cur on the action potential and transmembrane ion currents in rabbit ventricular myocytes to explore its antiarrhythmic property. The whole-cell patch clamp was used to record the action potential and ion currents, while the multichannel acquisition and analysis system was used to synchronous record the electrocardiogram and monophasic action potential. The results showed that 30 μmol/L Cur shortened the 50% and 90% repolarization of action potential by 17% and 7%, respectively. In addition, Cur concentration-dependent inhibited the Late-sodium current (INa.L), Transient-sodium current (INa.T), L-type calcium current (ICa.L) and Rapidly delayed rectifying potassium current (IKr), with the IC50 value was 7.53 μmol/L, 398.88 μmol/L, 16.66 μmol/L and 9.96 μmol/L, respectively. Importantly, the inhibitory effect of Cur on INa.L was 52.97-fold higher than that of INa.T. Moreover, Cur decreased ATX Ⅱ-prolonged APD, suppressed the ATX Ⅱ-induced early afterdepolarization (EAD) and Ca2+-induced delayed afterdepolarization (DAD) in ventricular myocytes, and reduced the occurrence and average duration of ventricular tachycardias and ventricular fibrillations induced by ischemia-reperfusion injury. In conclusion, Cur inhibited INa.L, INa.T, ICa.L and IKr, shortened APD, significant suppressed EAD and DAD-Like arrhythmogenic activities at the cellular level and exhibited antiarrhythmic effect at the organ level. It is first revealed that Cur is multi-ion channel blocker that preferentially blocks INa.L and may have potential antiarrhythmic property.